The right and ownership on cultural heritage of Ukraine, historical and cultural values of the Republic of Belarus - Мартыненко, Игорь Эдуардович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
Historical and cultural heritage of Ukraine is the most important part of world culture. Cultural heritage - a collection inherited from previous generations of mankind cultural heritage. Monuments of recognized objects with a set of two features: the cultural significance and legal recognition as such by including in the security registry. Components included in the term "cultural property" includes the concept of "cultural heritage". The ownership of cultural monuments in Ukraine are regulated by the Civil Code and the Law "On protection of cultural heritage." Civil legal protection of cultural property includes the entire set of civil-legal means to ensure the safety of values: strengthening the existing relations ownership of cultural property, the regulation of the cash and the acquisition of new rights. An important role is played by preventive means of protection, with the aim to prevent the destruction or damage of cultural property, and in some cases - to compensate the damage caused to them: combating mismanagement treatment of cultural values, the invalidation of transactions made with them; An obligation to restore the property to its original condition; cessation of activities posing a threat to objects of cultural heritage (monuments) or a center for cultural values, etc .; protection of the right of ownership of cultural and historical monuments. The purpose of this article: to reveal the contents of ownership of cultural heritage monuments and other cultural values; justify proposals for improving civil protection of cultural heritage. In accordance with Art. 17 of the Law "On protection of cultural heritage" monument than the monument of archeology can be in the state, communal or private property. All the archaeological sites, including under water, including associated movable objects are state property. These movable objects to be classified as a state of the Museum Fund of Ukraine, accounting and storage in the manner prescribed by law. In order to improve civil protection of cultural heritage, the ownership of the monuments of history and culture believe that the offer to establish new rules for determining the legal consequences of the discovery of the treasure, the essence of which is as follows: the owner of the land or other property where the treasure was hidden, and the person who discovers a treasure, are entitled to receive remuneration in the amount of value of the treasure. The remuneration is distributed between the parties in equal shares. It is proposed to create legal guarantees to ensure the safety of the court seized of cultural values due to their mismanagement of content.